2002
DOI: 10.1016/s1535-6108(02)00127-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct BH3 domains either sensitize or activate mitochondrial apoptosis, serving as prototype cancer therapeutics

Abstract: The "BH3-only" proteins of the BCL-2 family require "multidomain" proapoptotic members BAX and BAK to release cytochrome c from mitochondria and kill cells. We find short peptides representing the alpha-helical BH3 domains of BID or BIM are capable of inducing oligomerization of BAK and BAX to release cytochrome c. Another subset characterized by the BH3 peptides from BAD and BIK cannot directly activate BAX, BAK but instead binds antiapoptotic BCL-2, resulting in the displacement of BID-like BH3 domains that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
1,462
3
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,468 publications
(1,523 citation statements)
references
References 36 publications
45
1,462
3
13
Order By: Relevance
“…Using a large array of synthetic BH3 peptides, two groups later showed that some of these peptides (Bid, Bim and Puma) could directly induce oligomerization of Bax and Bak to release cytochrome c, whereas the others could not (Letai et al, 2002;Kuwana et al, 2005;Kim et al, 2006b). The term 'activator' was chosen to describe this particular ability.…”
Section: Direct Activation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a large array of synthetic BH3 peptides, two groups later showed that some of these peptides (Bid, Bim and Puma) could directly induce oligomerization of Bax and Bak to release cytochrome c, whereas the others could not (Letai et al, 2002;Kuwana et al, 2005;Kim et al, 2006b). The term 'activator' was chosen to describe this particular ability.…”
Section: Direct Activation Modelmentioning
confidence: 99%
“…When an apoptotic stimulus is received, the 'sensitizer' BH3-only proteins are activated, which bind to the pro-survival proteins to liberate the 'activator' BH3-only proteins that are now able to interact with Bax/Bak to induce apoptosis (Letai et al, 2002). Various groups have reported evidence to support the existence of the two proposed classes of BH3-only proteins.…”
Section: S130mentioning
confidence: 99%
See 1 more Smart Citation
“…Activators (initially this group was limited to Bid and Bim but was later extended to include Puma) are suggested directly to bind Bax and cause its activation. Sensitizers, on the other hand, lack this capacity, and their function is limited to binding to prosurvival Bcl-2 proteins, thereby liberating activators and contributing to apoptosis (Kuwana et al, 2002(Kuwana et al, , 2005Letai et al, 2002;Kim et al, 2006). However, a central prediction of this model is that the combined loss of activators blocks all Bax/Bak-dependent apoptosis, but this is not the case (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 They are activated by BH3-only proteins binding to the α2-α5 surface groove, [6][7][8][9][10][11][12] or for Bax, to the α1/α6 'rear pocket'. 13 Binding triggers dissociation of the latch domain (α6-α8) from the core domain (α2-α5), together with exposure of N-terminal epitopes and the BH3 domain.…”
mentioning
confidence: 99%